A novel outer-inner magnetic two degree-of-freedom piezoelectric energy harvester. (1st May 2023) - Tian, Libin; Shen, Hui; Yang, Qian; Song, Rujun; Bian, Yixiang
Graphical abstract: Highlights: The proposed harvester can offer an operation bandwidth of 12.8 Hz (5–17.8 Hz). The operating bandwidth and the harvested power are increased by 106.5% and 42%. New introducing magnets can help the inner beam pass through potential wells easily. The technique can achieve wide operating bandwidth under different excitation level. Abstract: Aiming to achieve the high-performance piezoelectric energy harvester under broadband vibrations, an outer-inner magnetic two-degree-of-freedom piezoelectric energy harvester is proposed in this paper. An original linear two-degree-of-freedom energy harvester can achieve two close resonances both with large voltage amplitudes, using its cut-out cantilever beam. Based on the linear two-degree-of-freedom harvester, a nonlinear two-degree-of-freedom harvester has been developed by introducing two opposite magnets. The proposed harvester incorporates another two opposite magnets into the original nonlinear two-degree-of-freedom system, aiming to further broaden its operating bandwidth. A lumped-parameter model is established to describe the response characteristics of the proposed harvester with different magnet distances ( D or d ). Compared with the original nonlinear two-degree-of-freedom system, numerical and experimental results demonstrate that the proposed harvester can offer a significantly wider operating bandwidth in a lower frequency range. In the optimal configuration ( D = 14 mm, d = 10 mm), the harvester can offer an operation bandwidth of 12.8 Hz (5–17.8 Hz) under 0.3 g excitation, generating a power of 133 µW. The operating bandwidth and the harvested power are increased by 106.5% and 42%, respectively (under the same excitation of 0.3 g). In addition, the new introducing magnet force can help the inner beam easily pass through the potential well barriers under lower excitation than the original nonlinear two-degree-of-freedom system. Compared with the original technique, the excitation level acquired for high-energy interwell oscillation of the optimal configuration is decreased by 34.8% (from 0.23 g to 0.15 g). Furthermore, the proposed harvester is able to efficiently harvest energy from broadband vibration under different excitation levels because of the hardening behavior or bistable behavior with different magnet distances.